Unruly objects: NFTs, blockchain technologies and bio-conservation. Issue 3 (1st November 2021) - Dumitriu, Anna; May, Alex; Velios, Athanasios; Sakki, Zoi; Korakidou, Veroniki; Marçal, Hélia; Panagiaris, Georgios
This article explores and challenges notions and methodologies of conservation, including the use of blockchain technologies as a means of establishing provenance of a physical BioArtwork, of the artist's documentation encapsulating their intentions and of the conservator's records required for the artwork's ongoing care. The exploration is done through a case study of an art project called 'Unruly Objects and Biological Conservation' created by Anna Dumitriu with support from Alex May. The artwork consists of three items containing RFID tags sealed in resin ‐ which point to the location of the artist's documentation. Therefore, the works physically include instructions for maintaining their inherent concepts and materiality for the benefit of the conservators. Such instructions can often be difficult to track down, or become disassociated from the artwork while the digital preservation of this storage method also poses its own set of questions. The works also include biological material including mud from a bacterial ecosystem known as a Winogradsky Column, living plant material and SARS-CoV-2 (coronavirus) RNA from a plasmid construct.